(untitled) (Південний архів (історичні науки), 2023)
The purpose of the study is to analyze various forms of activity of the clergy in the public life of the population of Boykivshchyna at the end of the 19th – in the 30s of the 20th century. In the process of writing the article, the methods of analysis and synthesis, generalization, and the retrospective, chronologic, prosopographic, comparative-historical methods were used. The results. Priests of Boykivshchyna actively worked in a number of public associations. In the reading rooms of «Prosvita» they found a favorable ground for various forms of work, such as speeches with abstracts, campaign speeches, and loud readings. Such actions were aimed at eliminating illiteracy, expanding the horizons of villagers, providing them with basic information about geography, medicine, and rational management of the economy. For example, M. Zubrytsky introduced parishioners to the basics of legal culture, as he interpreted laws and regulations. Parishioners developed a network of choirs and theater circles, seeing them as an important component of cultural and educational work and an opportunity to involve villagers in the best examples of Ukrainian and world culture. Often amateur circles were led by the children of priests. The pastors of Boykivshchyna initiated school plebiscites in support of the Ukrainian language of instruction. They urged the peasants to organize kindergartens. The clergy popularized the ideas of cooperation, as well as a healthy lifestyle. During the first communion, the priests demanded an oath not to drink alcohol until the age of 21, organized sobriety missions, symbolic funerals of horivka. Pastors campaigned for elections to local authorities, convened meetings on election legislation and even monitored the voting process. Conclusions. At the end of the 19th – 30s of the 20th century. the clergy of Boykivshchyna actively worked for the sake of increasing the cultural and educational and socio-economic living standards of the villagers. It took care of the formation of the foundations of the legal culture of citizens, ensured their active participation in pre-election processes, because it saw this as one of the prerequisites for a successful socio-political struggle.